Análisis a la revictimización en casos evidenciados por delito de abuso sexual en el cantón Durán - Atauchi Siguencia, José Luis (2023)
Re-victimization is the product of inappropriate behaviors carried out by justice operators and auxiliary institutions in the criminal process, leading to this problem being presented in the absence of specific regulations to not re-victimize the person who has been injured by the crime. victimizer in crimes of sexual abuse, this during his intervention or repetitive diligence, continuously exposing the victim to the trauma caused, subjecting her to numerous examinations, interrogations and cross-examinations. In the present work, we seek to prevent the re-victimization of the victim in cases of sexual abuse crimes, this through means of field verification such as surveys and statistics of specific data that serve as an instrument for the collection of information, taking this in consideration of collecting information on the cases reported in the Duran Canton, and followed up by the State Attorney General's Office in 2021-2022. Some identifiable variables can be used so that the study can verify their consensual relationships, directly where measurable, observable and quantifiable data are collected, and the collection instruments that will be able to identify relevant aspects for the analysis of the results, and that served to elaborate the conclusions and recommendations, which emphasize the need for reforms to be made to the Organic Comprehensive Criminal Code of follow-up and proceedings in the current criminal process to avoid secondary re-victimization.